Las mujeres de la elite lambayecana 1720 - 1820. Una historia de la vida cotidiana. - Reyes Aguilar, Emerita Elizabeth (2019)
The purpose of this paper was to meet the women of the Lambayecan elite during the years 1720 to 1820, with the objective of analyzing the participation of women both within their home and in society, from the different changes that occurred during the century XVIII. _x000D_ At the same time, the historical context of the town of Lambayeque has been studied, taking into account the social and economic aspect, in order to understand how it influenced the elite, since Lambayecan society was divided into different social groups (Spanish, indigenous, castes); Likewise, its economy was based on agriculture and cattle raising that had a great boom, especially the cultivation or production of sugarcane, which helped the population to consolidate its economy. _x000D_ In this investigation, the image and situation of the woman within the family was analyzed as a consequence of a patriarchal order that granted the male his tutelage since he was considered incapable of making his own decisions, being often used as a means of exchange that was given in exchange for prestige and money, through marriage that was the basis for the formation of society. In order to carry out the research it was necessary to analyze both books, dowry letters, testaments, ecclesiastical, criminal and civil causes in order to know the status of each family and to what extent the woman could participate both at home and in public. _x000D_ Thus, through the primary and bibliographic sources it is verified that women were not always dependent since they took charge of their family when it was necessary due to laziness, abandonment or death of their husband, becoming the heads of the household. It can also be said that women with greater independence were widows because they were able to make transactions of buying and selling goods without the need of a permit. _x000D_ Finally, women could also file complaints and be denounced for a fault committed, for abuse, or to defend their honor and honor. The demands could be towards her husband for mistreatment and food, as well as for fights that were generated between women or with a neighbor.